THEORIES OF INTERNATIONAL RELATIONS - Afonso, Henrique Weil (Revista Ética e Filosofia Política, 2018)
Global society is going through relentless transformations as different concerns and threats arise. The end of the Cold War has brought to the fore ancient ethnic rivalries, with sectarian nationalist movements mushrooming in former Soviet Union states. Bipolarity, according to realists, has kept the world safe from a major scale nuclear encounter, whereas liberal assertions related to the spread of universalist values as a means to increase the prospects for peace are still very influential. In an ever-connected world, states that opt for an isolationist stand are doomed to face the disapproval of the international community, finding it increasingly hard to meet domestic economic, social and political demands.